Perbedaan Penurunan Kesadahan dengan Penyaringan Tipe A dan Tipe B - Agung Kurniawan; Haryono Haryono; Tuntas Bagyono (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
Jalakan Village in Pandak District, Kabupaten Bantul has the characteristics of limestone hills. The source of clean water of the residents contained levels of hardness of 391 mg/l CaCO3. The study was aimed to decrease the water hardness by implementing two types of filtration, by con-ducting a quasi experiment with pre-test post-test design. As the study object was local water company (PAM-Des) distribution in one of the consumer's house. The distribution water was fil-tered using Type A filter (5 cm activated carbon, 14,5 cm cation resin) and Type B (5 cm activa-ted carbon, 9,5 cm zeolite, 5 cm cation resin). The flow of water debit into the filter housing is 500 ml/minute, with 82,44 seconds contact time, and filtration capacity as much as 720 l/day. The Type A filter can reduce hardness level 72,93 %, higher than that of Type B which was 67,58 %. Data analysis with independent sample t-test obtained p-value of 0,013, which means that the different decrease is significant.